2018
DOI: 10.1021/acsnano.8b02832
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Order in Dewetted Block Copolymer Thin Films on Chemically Patterned Surfaces

Abstract: We investigated the dewetting process on flat and chemically patterned surfaces of ultrathin films (thickness between 2 and 15 nm) of a cylinder forming polystyrene- block-poly(methyl methacrylate) (PS- b-PMMA) spin coated on poly(styrene- r-methyl methacrylate) random copolymers (RCPs). When the PS- b-PMMA film dewets on a 2 nm-thick RCP layer, the ordering of the hexagonally packed PMMA cylinders in the dewetted structures extends over distances far exceeding the correlation length obtained in continuous blo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…After the thermal treatment, the formation of droplets periodically distributed within the prepatterned structures is observed (Figure b,c). As previously reported, the height of the droplets linearly scales with their diameter; thus, the maximum height reached by the droplet, shown in Figure c, is ∼95 nm.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…After the thermal treatment, the formation of droplets periodically distributed within the prepatterned structures is observed (Figure b,c). As previously reported, the height of the droplets linearly scales with their diameter; thus, the maximum height reached by the droplet, shown in Figure c, is ∼95 nm.…”
Section: Resultssupporting
confidence: 85%
“…In the case of BCPs treated at T a below the ODT, stable films not subjected to the rupture process are observed when h > 2· R g . In contrast, when h < 2· R g , dewetting processes occurs with ε ∼ 1. , This behavior suggested the occurrence of an additional stabilizing effect of the BCP nanometric morphology for h > 2· R g .…”
Section: Resultsmentioning
confidence: 95%
“…McGraw et al studied the terracing of a lamellar BCP in a ring-shaped droplet of material . Lupi et al demonstrated the formation of single-grain hexagonal morphologies in ultrathin dewetted droplets of BCP cylinder-forming material . Printing methods have been applied to creating isolated patterns of BCP film material .…”
Section: Introductionmentioning
confidence: 99%
“…[ 29,45 ] At the same time, a reduced effective glass transition temperature imposed by the so‐called “wet brush” regime [ 29 ] significantly affects the thermal stability of the BCP film. As a result, a low‐temperature dewetting process, typically occurring in ultrathin (sub‐10 nm) films, [ 46 ] takes place on relatively thick BCPs. [ 36 ]…”
Section: Resultsmentioning
confidence: 99%